PERILAKU PEMBELIAN IMPULSIF MERCHANDISE K-POP PADA REMAJA WANITA KOMUNITAS STAY DITINJAU DARI GAYA HIDUP - Nada Annisau Ulya; Igaa Noviekayati; Aliffia Ananta (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2022)
K-pop fans have a habit of buying popular idol merchandise. Merchandise purchases become impulsive if done continuously, spontaneously, and suddenly. One of the factors influencing this impulsive purchase is lifestyle. The purpose of this study is to find out the relationship between lifestyle and K-pop merchandise impulsive purchase behavior in adolescents’ women of STAY community in Surabaya. The subjects in the study involved 102 adolescents’ women joining the STAY community in Surabaya and a population of 138. Sampling retrieval techniques use purposive sampling techniques with quantitative research designs. Hypothesis testing using the product moment correlation test obtained a score of 0.654 with significance p = 0,000 (P<0,01) indicating that there is a significant positive relationship between lifestyle and impulsive buying behavior of K-pop merchandise in female adolescents of the STAY community in Surabaya. So, it can be interpreted that the higher one's lifestyle, the higher the impulsive buying behavior of K-pop merchandise in adolescents’ women of STAY community in Surabaya.